Tendencies in the social policy of the Republic of Bashkortostan ("Journal "U". Economy. Management. Finance.", 2019)
The article presents an analysis of social policy in the Republic of Bashkortostan. The main problems in its implementation and possible solutions are considered.
Keywords: social policy; social protection; Republic of Bashkortostan